Dissecting achievement motivation: Exploring the link between states, situation perception, and trait-state dynamics - Witte, Katja; Spinath, Birgit; Ziegler, Matthias (Learning and individual differences, 2024)
Achievement motivation is an important predictor for academic performance. For a better understanding of the mechanisms explaining this relation, it is necessary to shift from a trait to a state perspective to unravel underlying dynamic processes and take the influence of the situation into account. However, there were only few empirical attempts to analyze achievement motivation at the within-person level and they did not yet investigate relations to situation perception. Hence, we examined whether achievement motivation traits manifest as states and if those are related to specific situation characteristics. Utilizing the experience sampling method (N = 8,592 assessments), we obtained self-reports from N = 223 school and university students and applied multilevel modeling. Results revealed fluctuation of achievement motivation at state level and exclusive relations with situation characteristics (especially Duty and Intellect) for various motivational constructs. We discuss theoretical and practical implications as well as prospects for future studies. - Educational relevance and implications statement - Since achievement motivation (along with other variables such as cognitive abilities) can predict academic performance and it is important to understand the processes behind it, it would be appropriate to analyze achievement motivation not only as a (relatively stable) traitlike variable, but to consider high-frequency fluctuations (states). A person's motivation can vary from situation to situation (i.e., depending on how a situation is perceived, people may be more or less motivated). The results of the current study show that there are (1) situational variations in achievement motivation and (2) relations of these states with specific situational characteristics for various motivational constructs. In practical terms, learning environments could be enriched to stimulate the perception of certain situation cues in such a way that Duty and Intellect are elicited, which then potentially enhances motivation. One possibility would be, for example, to stress in a learning situation the potential of actually learning something of intellectual value.